The Age, Education, and Occupation Characteristics is not Associated with Human Immunodeficiency Virus (HIV) Infection in Pregnant Mothers - Saspriyana, Kade Y. (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To know the relationship between age, education and occupation on the pregnant women and the HIV status of the husband against the risk of being infected with HIV. Method: This was an unpaired case control study performed in the Obstetrics and Gynecology Department of Sanglah Hospital, Denpasar, from October to November 2011. The subjects were pregnant women who were willing to participate in the research, which were grouped into HIV-infected case and control group. Diagnosis of HIV was based on rapid test. The data was analyzed using Chi Square test with the help of SPSS version 17.0 Result: There was fifty subjects consisting of 25 subjects in the case group and 25 subjects in control group we obtained that the risk of HIV-infected pregnant women in the old vs young age, low vs higher education, and occupations at risk vs not at risk is not significant in the two groups. Each Odds ratio is 0.35 (CI = 95% 0.08-1.55; p = 0.16), 0.85 (CI = 95% 0.28-2.59; p = 0.77), and 2.09 (CI = 95% 0.18-24.62; p = 1.00). Meanwhile, the odds ratio of the husband HIV status was 12.67 (CI = 95% 3.31-48.50; p = 0.01). Conclusion: Husbands infected with HIV increases the risk of HIV in pregnant women 12 times greater than if the husband was not infected with HIV. Whereas, age, education, and the occupation of mothers is not a risk factor for the occurrence of HIV infection in pregnant women. [Indones J Obstet Gynecol 2014; 2: 65-68] Keywords: age, education, husband HIV status, occupation and pregnant women infected with HIV.